2004
DOI: 10.1209/epl/i2004-10020-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of high-energy electron generation through suppression of Raman backscattering

Abstract: The effect of Raman backscattering (RBS) on high-energy electron generation in laser-plasma interaction has been investigated for laser intensities well above the wave breaking and electron trapping threshold. One-dimensional particle-in-cell simulations show that suppression of RBS increases the high-energy electron yield in this regime. RBS-induced heating causes heavy beam loading and damping of the laser wake. Its suppression leads to higher wake amplitudes and higher particle energies. RBS suppression thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…In this paper, we investigate the role of Raman backscattering (RBS) in highenergy electron production and the interplay between RBS and Raman forwardscattering (RFS) in the high-intensity regime of a self-modulated LWFA [13]. In previous work [5,[14][15][16][17][18][19], it has been demonstrated that the presence of RBS leads to the production of mildly energetic electrons.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we investigate the role of Raman backscattering (RBS) in highenergy electron production and the interplay between RBS and Raman forwardscattering (RFS) in the high-intensity regime of a self-modulated LWFA [13]. In previous work [5,[14][15][16][17][18][19], it has been demonstrated that the presence of RBS leads to the production of mildly energetic electrons.…”
Section: Introductionmentioning
confidence: 99%